Bow Hunter's Syndrome: A rare cause of vertebrobasilar insufficiency - Maria Montano, MD, MPH; Kristin Alman, DO; Michelle J Smith, MD; Garen Boghosian, MD; William S Enochs, MD, PhD (Radiology Case Reports, 2021)
Bow Hunter's syndrome, also referred to as rotational occlusion of the vertebral artery, is caused by dynamic compression of a patient's dominant vertebral artery. We reported a case of successful clinical and imaging work up of Bow Hunter's Syndrome that occurred in a 79-year-old female patient. We discussed the clinical presentation, imaging findings, and subsequent management options of this rare syndrome. The gold standard for diagnosis is dynamic cerebral angiography, which allows the reproduction of symptoms with head turn greater than 30-45 degrees. Subsequent management is based on the underlying etiology causing rotational compression.